596 Armed myxoma virus demonstrates therapeutic activity in xenograft models. (10th December 2020) - Torres-Dominguez, Lino; Franco, Lina; Abrantes, Mario; Walker, Benjamin; Tacner, Zachary; Kien, Cassandra; Elliott, Natalie; Waters, Anna; McFadden, Grant; Potts, Steven; Sharp, Leslie
Abstract : Background: Oncolytic Viruses (OV) selectively replicate in and lyse tumor cells and provide stimulation to the immune system. This represents a promising therapeutic option for cancer patients that do not respond well to treatment with immune checkpoint inhibitors. Myxoma virus (MYXV) is a member of the Pox family of double stranded DNA viruses. The natural host of MYXV is a subset of rabbits and hares, but MYXV is able to infect cancer cell lines of humans and other species. The genome of MYXV is relatively large and is amenable to engineering for expression of transgenic proteins making it an excellent oncolytic virus for introduction of immunomodulatory proteins. Methods: The current work describes the in vitro oncolytic activity and transgene production capability in human cancer cell lines, and in vivo activity of armed myxoma viruses in xenograft human cancer models. Results: Armed Myxoma viruses demonstrate transgene production and oncolytic activity in multiple human cancer cell lines in vitro and in vivo Conclusions: Armed Myxoma viruses present a novel oncolytic viral therapy with ability to modulate immune responses in human cancer models Ethics Approval: This study was approved by OncoMyx Therapeutics and the TD2 IACUC